Analysis of Financial Statement Fraud Using the Beneish M-Score Method: A Study of Companies Involved in Legal Cases in Indonesia - Ramdany Ramdany; Susi Susilawati; Maria Suryaningsih; Ridwan Saleh; Samukri Samukri (Greenation Research & Yayasan Global Resarch National, 2026)
The purpose of this study is to analyze financial statement fraud using the Beneish M-Score method. The main variables utilize indicators from eight financial ratios: Day Sales in Receivables Index (DSRI), Gross Margin Index (GMI), Asset Quality Index (AQI), Sales Growth Index (SGI), Depreciation Index (DEPI), Selling, General, & Admin Expenses Index (SGAI), Leverage Index (LVGI), and Total Accruals to Total Assets (TATA) to generate the M-Score value. Companies are suspected of committing financial statement fraud if they have an M-Score value greater than -2.22.The population in this study consists of 40 companies listed on the Indonesia Stock Exchange, comprising 20 companies suspected of committing financial statement fraud and 20 companies suspected of not committing financial statement fraud. The research results show that among the 20 companies suspected of committing financial statement fraud, 9 companies have M-Score values greater than −2.22. Meanwhile, among the 20 companies suspected of not committing financial statement fraud, 3 companies have M-Score values greater than −2.22.